Analysis Security of SIA Based DSS05 on COBIT 5 Using Capability Maturity Model Integration (CMMI) - Handoyo, Eko; Umar, rusydi; Riadi, Imam (Universitas Negeri Semarang, 2019)
A secure academic information system is part of the college. The security of academic information systems is very important to maintain information optimally and safely. Along with the development of technology, academic information systems are often misused by some irresponsible parties that can cause threats. To prevent these things from happening, it is necessary to know the extent to which the security of the academic information system of universities is conducted by evaluating. So the research was conducted to determine the Maturity Level on the governance of the security of University Ahmad Dahlan academic information system by using the COBIT 5 framework on the DSS05 domain. The DSS05 domain on COBIT 5 is a good framework to be used in implementing and evaluating related to the security of academic information systems. Whereas to find out the achievement of evaluation of academic information system security level, CMMI method is needed. The combination of the COBIT 5 framework on the DSS05 domain using the CMMI method in academic information system security is able to provide a level of achievement in the form of a Maturity Level value. The results of the COBIT 5 framework analysis of the DSS05 domain use the CMMI method to get a Maturity level of 4,458 so that it determines the achievement of the evaluation of academic information systems at the tertiary level is Managed and Measurable. This level, universities are increasingly open to technological developments. Universities have applied the quantification concept in each process, and are always monitored and controlled for performance in the security of academic information systems.